Red line American foreign policy in a time of fractured politics and failing states - Crowley, P. J. (Rowman & Littlefield, 2017)
Former Deputy Secretary of State P. J. Crowley unpacks the legacy of American triumphs and failures in Iraq. He argues that presidents has fallen victim to the Iraq Syndrome-the disconnect between politics, policy, strategy, and narrative-that has hampered America's foreign policy in the Middle East and hotspots throughout the world. In order to maintain America's global leadership role, Crowley argues that the next president must realign American's national security politics, policies, strategies, and narrative for the long term.